Finite-element modeling of the electro-thermal contacts in the spark plasma sintering process. Issue 3 (February 2016) - Manière, C.; Pavia, A.; Durand, L.; Chevallier, G.; Afanga, K.; Estournès, C.
Abstract: Spark plasma sintering (SPS) is a breakthrough process for powder consolidation assisted by pulsed current and uniaxial pressure. In order to model the temperature variations of the tools during a SPS cycle, the Graphite-Papyex-Graphite contact phenomena are studied experimentally and modeled by finite element calculations. Compared to conducting materials, the thermo graphic image of an insulating sample (alumina) shows strongly localized heating along the Papyex implying contact effects are predominant. The aim of this modeling study is to determine the main contact phenomena due to Papyex. It is based on numerous experimental data and studies the case of alumina sintering. Finally the contact model is confronted to experimental thermal images.